2013
DOI: 10.1007/s00167-013-2419-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot rotation on the mechanical axis and correlation between knee and whole leg radiographs

Abstract: Foot position of ER could show less varus alignment and the reverse could occur in the IR position, compared to the neutral foot position. The severity of varus alignment could be underestimated in the local radiograph, compared with that of whole leg radiograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 13 publications
1
55
0
11
Order By: Relevance
“…The anatomical axis of the femur is at 6 degrees of valgus from the mechanical axis of the lower limb and 9 degrees of valgus from the true vertical axis of the body [7]. A previous study reported that foot rotation can affect the mechanical axis of the lower extremities [12]. Rotation of the bone through the right-angled cutting plane to the anatomical axis of the femur can affect the alignment of the lower leg.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical axis of the femur is at 6 degrees of valgus from the mechanical axis of the lower limb and 9 degrees of valgus from the true vertical axis of the body [7]. A previous study reported that foot rotation can affect the mechanical axis of the lower extremities [12]. Rotation of the bone through the right-angled cutting plane to the anatomical axis of the femur can affect the alignment of the lower leg.…”
Section: Discussionmentioning
confidence: 99%
“…Ротация большеберцовой кости обуслов-ливает избыточную нагрузку на суставные поверхности надколенника, а также ограни-чивает вращательные движения (боковые) надколенника во фронтальной плоскости, практически не затрагивая поступатель-ных (сгибание/разгибание) [29,37]. Особен-ности влияния ротации большеберцовой кости зависят также от её механизма -ла-теральный или медиальный ротационный компонент.…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
“…В частности, Lee и соавт. докладывали, что наружная ро-тация на 10-15° от нейтральной позиции достоверно увеличивает пик нагрузки ло-кально на большую латеральную фасет-ку [31,37]. При наружной ротации больше-берцовой кости страдает и медиальная су-ставная поверхность надколенника, в том числе и «спящие» фасетки.…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
See 2 more Smart Citations